Pengaruh Makroekonomi, Capital Adequacy Ratio, Loan To Deposit Ratio dan Pertumbuhan Kredit terhadap Non Performing Loan pada Bank Asing di Indonesia Periode 2013-2014 - Maya Rosita; Musdholifah Musdholifah (Universitas Negeri Surabaya, 2018)
The aim of this study was to understand the influence of macroeconomic factors in this research are exchange rate and inflation, while for the internal bank are capital adequacy ratio (CAR), loan to deposit ratio (LDR) and credit growth towards non performing loan (NPL). The data that used is quarterly data from financial statements of Foreign Bank in Indonesia period of 2013 until 2014. Data analysis method used is multiple-regression analysis. The results showed that there was a simultaneous influence of independent variables towards NPL of Foreign Bank in Indonesia. However, partially showed that CAR has a negative influence, the higher capital adequacy ratio, it can serve to accommodate the risk of losses faced by banks due to the increase in non performing loans. LDR has a positif influence, LDR shows expansion of bank loans made to measure current or whether bank intermediary function. LDR which leads to high risk of uncollectible loans to be high which will result in a non performing loans.